Rheological study of linear high density polyethylenes modified with organic peroxide - Pérez, Claudio Javier (2002)
Four high density polyethylenes were modified using different concentrations of an organic peroxide in order to change their molecular structure. The effects of the presence of vinyl groups in the original polymer molecules and of the peroxide concentration used in the modification process were analyzed. All the concentrations of peroxide used in this study were below the critical concentration that produces a macroscopic molecular network. The weight-average molecular weight of all the polyethylenes augments and the molecular weight distribution gets wider as the concentration of peroxide increases. These results support the general belief that the chain-linking reactions dominate the modification process. Evidence of the important role played by the vinyl groups is found not only in the change of the width of the chromatograms but also in the position of their maximums. The vinyl-containing polymers display the largest molecular changes for a given peroxide content. The magnitude of the viscous and elastic moduli of the polyethylenes goes up as the concentration of peroxide used increases showing the effect of the generated large molecules. The linear viscoelastic response of the modified polymers is thermorheologically complex. This complexity can be associated with the generation of branched molecules. For similar molecular weights and peroxide concentration, the flow activation energy displayed by the polyethylenes with larger concentration of vinyl groups is larger. This result suggest that a much more complex molecular structure is formed in the presence of vinyl groups. The dynamic moduli of the polymers were analyzed using the generalized viscoelastic model. The spectrum of relaxation times was determined for each polymer and analyzed as a function of the peroxide concentration. © 2002 Elsevier Science Ltd. All rights reserved.